Cold water ingestion ameliorates increase in core temperature and discomfort during simulated motor racing in a hot environment: a randomized trial - Bird, Stephen Richard; Troynikov, Olga; Watson, Chris; Cohen, Marc; Sostaric, Simon (Frontiers in Sports and Active Living, 2025)
IntroductionFormula One and other motor car racing drivers race for prolonged periods in hot conditions wearing protective apparel that impairs heat loss. They are thus at risk of a significantly elevated core temperature. The aims of this study were to determine whether the voluntary ingestion of cold fluid aided thermoregulation more effectively than the voluntary ingestion of ambient temperature fluid in a simulated motor racing environment.MethodsEight male participants commenced two 120-min simulated motor racing trials in an environmental chamber (40°C, 50% humidity). During one trial they were provided with 1 L of ambient temperature water (AWT), whilst in the other trial the water temperature was ∼5°C (CWT). A drinking schedule of “1 sip every four minutes” was advocated. Participant core temperature, skin temperature and heart rate were recorded continuously, whilst thermal comfort, response time and cognitive function were assessed at 30-min intervals.ResultsAll participants successfully completed their CWT, but only two completed the full 120-mins of their AWT (AWT trial duration ranged from 80 to 120 min). Despite encouragement to drink more, both the rate of consumption (AWT 333 ± 103 v CWT 436 ± 99 ml/h) and total volume of water consumed (AWT 585 ± 233 v CWT 872 ± 198 ml) were less in the AWT (p < 0.005). At the 75-min point of the trials, participant core temperatures had increased by 1.26 ± 0.29 in AWT and 0.81 ± 0.30 in CWT. Furthermore, at the point of trial cessation, core temperature in the AWT had increased by 1.69 ± 0.36°C, but only 1.17 ± 0.52°C in the CWT (p < 0.05). Participants reported less discomfort and a lower rating of perceived exertion during the CWT. In both trials, response time to the cognitive test decreased as the trials progressed, with no evident difference in response time nor cognitive function between the two trials.DiscussionThe ingestion of cold water was associated with an ability to continue with volitional performance and associated with an ameliorated increase in core temperature as well as providing psychological benefits of cold “refreshment”.